A Study on The Skills and Effectiveness of the Innovative Suction Skill Mannequin in Infants Made from Natural Rubber in Second-year Nursing Students, Boromarajonani College of Nursing, Songkhla - Prommul, Jirarat; Mangme, Tuangporn; Perngyai, Chutima; Intaranarong, Kritika; Klerlhee, Chanyanuch; yangtong, Soraya (Princess of Naradhiwas University Journal, 2026)
Background and Objectives Laboratory practice with mannequins is crucial for developing nursing skills in nursing students, especially for suctioning infants who cannot cough up sputum on their own. Suctioning helps reduce airway obstruction and oxygen deficiency, making it easier for infants to breathe. The infant suctioning mannequin developed from natural rubber is used to enhance confidence, proficiency, and accuracy in practice, thereby improving infant safety. The objectives were as follows: 1) Compare suctioning skills using the innovative mannequin with the criterion at 80%; 2) Compare the effectiveness of the mannequin with the average criterion of up to a good level (>3.50). Methods This was a quasi-experimental study. The sample consisted of 45 second-year nursing students, selected through simple random sampling without replacement. The research instruments used were 1) the natural rubber infant suction skill innovation mannequin, and 2) a questionnaire on skills and effectiveness of the natural rubber infant suction skill innovation mannequin. The item-objective congruence (IOC) ranged from 0.67 to 1.00, and the questionnaire reliability had a Cronbach's alpha coefficient of 0.77. Data analysis used descriptive statistics such as frequency, percentage, mean, and standard deviation, as well as the one-sample t-test. Results The results found that as follows: The average score of suction skill of the natural rubber infant suction skill mannequin was 90.06 (SD = 10.92), which was significantly higher than the predetermined criterion of 80% at a statistical significance level of .001. The average effectiveness score of the natural rubber infant suction skill mannequin was 4.69 (SD = 0.34), which was significantly higher than the predetermined criterion of 3.50 at a statistical significance level of .001. Conclusion and Recommendations The natural rubber infant suction skill mannequin can be used in academic settings for teaching and learning pediatric and adolescent nursing in both laboratory and practical settings and for allowing students to practice independently until they gain confidence before practicing with real patients. The natural rubber infant suction skill mannequin should be developed further by improving the completeness of the structure according to anatomical principles.